Compilations of court decisions of legal responsibility in the pharmaceutical industry - O. O. Molodozhonova (Zaporozhye State Medical University, 2016)
Aim. Identify and summarize issues of legal responsibility in the pharmaceutical industry of Ukraine. Methods and results. The author analyzed cases, which deal with liability among Court materials that are freely available to the public. The author reviewed more than 100 cases of claims to the courts, which deal with persons involved in pharmaceutical field, 94 cases of which were relevant study problems. Conclusion. The author provided forensic analysis of pharmaceutical liability in pharmacy and compared the cases ratio in different regions of Ukraine. The author found that during 2006-2014 years the highest proportion of cases number was observed in Kyiv (12.77%), Donetsk (11.70%) and Odessa (9.57%) regions and the lowest share, respectively, in Kirovograd (1.06%), Luhansk (1.06%) Rivne (1.06%), Chernivtsi (1.06%) and Chernihiv (1.06%) regions. The author set the proportion of criminal cases brought against pharmaceutical workers and systematized punishment for criminal proceedings. The author set the proportion of civil cases investigated during forensic analysis of pharmaceutical workers offenses committed during the occupation. The author systematized grounds lawsuits against pharmaceutical workers under the Civil Code of Ukraine. The author set the proportion of administrative cases investigated during forensic analysis of pharmaceutical workers offenses committed during the occupation.